DESIGN OF LOGISTICS COMPANY PERFORMANCE MEASUREMENT - Aried Sumekar; Erlina Erlina; Rina Br. Bukit; Chandra Situmeang (Universitas Kristen Indonesia Toraja, 2022)
Bubu Logistic Indonesia is a service company. Based on company reports the performance of the operational system shows quite good results, but integrated performance measurement has never been carried out. This study aims to design a performance measurement PT. Bubu Logistic Indonesia with several integrated aspects, namely financial perspective, customer perspective, internal business process perspective, as well as learning and growth perspective which will improve the performance of employees of PT. Bubu Logistics Indonesia. This research is a design process of measuring the performance of employees of PT. Bubu Logistic Indonesia uses the Analytical Hierarchy Process (AHP) and Balance Scorecard (BSC) methods. To find out the results of designing employee performance measurements, the next step is to make a strategic map that has been proposed and approved by management and then grouped into 4 Balance Scorecard (BSC) perspectives. To find out the weight and priority of each perspective, the Analytical Hierarchy Process (AHP) method is used. The financial perspective has a weight of 39.25%, followed by a customer perspective of 36.75%, an internal business perspective has a weight of 18.75%, and a growth and learning perspective has a weight of 5.25%. From the results of measuring the performance of employees of PT. Bubu Logistic Indonesia has an average performance measurement score for 6 months of 56%.